PENGARUH KECERDASAN EMOSIONAL PERILAKU BELAJAR DAN KECERDASAN SPIRITUAL TERHADAP TINGKAT PEMAHAMAN AKUNTANSI (Studi Kasus Pada UNISRI, UNIBA dan UNSA) - Fajar Nurul Ikhsan; Rispantyo Rispantyo; Sunarti Sunarti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
This study aims to determine the effect of emotional intelligence, learning behavior and spiritual intelligence on the level of understanding of accounting. This research was conducted on accounting study program students at UNISRI, UNIBA and UNSA, and the type of data used is quantitative data. The data source used is primary data. The entire population in this study were eighth semester students (8), samples that had taken 12 courses including: Introduction to Accounting, AKM 1, AKM 2, AKL 1, AKL 2, Auditing 1, Auditing 2, Cost Accounting, Accounting Systems, Accounting Public Sector, Accounting Information Systems, Accounting Theory. The sampling technique is done by using purposive sampling method. In this study shows that emotional intelligence learning behavior has a significant positive effect on the level of understanding of accounting, and spiritual intelligence has a significant positive effect on the level of understanding of accounting.